Otoritas dan validitas hadis dalam praktik keagamaan kontemporer di era digital - Mubarok, Muhammad Syafi'ul (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has significantly transformed the ways in which hadith are produced, disseminated, and practiced in contemporary Muslim religious life. Rapid access to religious content through social media and digital platforms has driven a shift in hadith authority from traditional scholarly institutions to non-academic figures, such as da‘wah influencers. This condition raises serious problems concerning the validity of hadith, particularly the widespread use of da‘if hadith without adequate verification of sanad and matan. This study aims to analyze the dynamics of hadith authority and validity in contemporary religious practices in the digital era using a qualitative, library-based research approach. The analysis focuses on the relationship between digital religious authority, hadith critical literacy, and the application of classical methodologies such as naqd al-sanad in new contexts. The findings indicate that weak methodological literacy among the public and the dominance of digital authority contribute to distortions in the understanding of hadith. Therefore, this study emphasizes the urgency of strengthening hadith literacy and adapting hadith criticism methodologies that are relevant to the digital ecosystem in order to preserve the authority and validity of hadith in modern religious practice.